The Burden of Osteoarthritis in the Middle East and North Africa Region From 1990 to 2019 - Shamekh, Ali; Alizadeh, Mahasti; Nejadghaderi, Seyed Aria; Sullman, Mark J. M.; Kaufman, Jay S.; Collins, Gary S.; Kolahi, Ali-Asghar; Safiri, Saeid (Frontiers in Medicine, 2022)
Objective: We aimed to report the most current data on the prevalence, incidence, and years lived with disability (YLDs) associated with osteoarthritis (OA) for the 21 countries and territories located in the Middle East and North Africa (MENA) region from 1990 to 2019 by age, sex, cause, and sociodemographic index (SDI). Methods: Publicly available data from the Global Burden of Disease 2019 study were used to report the OA-related burden. Estimates are reported as counts and age-standardised rates, along with their corresponding 95% uncertainty intervals (UIs). Results: In 2019, the age-standardised prevalence of OA in MENA was 5342.8 per 100,000 (95% UI: 4815.9-5907.8), which is 9.3% higher than in 1990 (8.1%-10.5%). Similarly, the age-standardised annual incidence of OA per 100,000 was 430.4 (382.2-481.9), demonstrating a 9.4% increase since 1990 (8.3-10.5). OA was the cause of 185.4 (92.8-370.2) age-standardised YLDs per 100,000 in 2019, which was 10% higher than in 1990 (8.7-11.4). Saudi Arabia, Kuwait, and Iran had the highest OA burden in MENA, while Yemen, Afghanistan, and Sudan had the lowest burden. In all MENA countries, OA affected more women than men, had an increasing burden with increased age, and had the highest impact on the knee, hip, and hand joints, respectively. OA was also positively associated with the SDI. Conclusion: The burden of OA increased over 1990-2019 in the MENA region. The study emphasizes the importance of early preventative approaches in order to control any future health, economic, and quality of life crises imposed by OA in this region.